2005
DOI: 10.1007/s00213-005-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms involved in the asymmetric interaction between cannabinoid and opioid systems

Abstract: The aim of this work was to study the mechanism of cross-modulation between cannabinoid and opioid systems for analgesia during acute and chronic exposure. Acute coadministration of ineffectual subanalgesic doses of the synthetic cannabinoid CP-55,940 (0.2 mg/kg i.p.) and morphine (2.5 mg/kg i.p.) resulted in significant antinociception. In chronic studies, a low dose of CP-55,940 (0.2 mg/kg, i.p.) that per se did not induce analgesia in naive animals produced a significant degree of antinociception in rats ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 38 publications
(61 reference statements)
4
42
0
Order By: Relevance
“…In animals, subchronic THC exposure can decrease the density and expression of cannabinoid CB 1 receptors in many areas of the brain, and pharmacodynamic changes such as these underlie tolerance to cannabinoids (Maldonado, 2002). Behavioral sensitization induced by repeated acute exposure to cannabinoid agonists is associated with increased intracellular activation of CB 1 receptors in the caudate putamen and cerebellum (Rubino et al, 2003; see also Rubino et al, 2004), increased m-opioid receptor binding in the lateral thalamus and periaqueductal gray (PAG), and increased intracellular activation of m-opioid receptors in the nucleus accumbens (Viganò et al, 2005). Using a THC pre-exposure regimen that increases heroin intake in rats under an FR1 schedule, Ellgren et al (2007Ellgren et al ( , 2008 found lasting alterations of both the cannabinoid and opioid systems in rats exposed to THC during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, subchronic THC exposure can decrease the density and expression of cannabinoid CB 1 receptors in many areas of the brain, and pharmacodynamic changes such as these underlie tolerance to cannabinoids (Maldonado, 2002). Behavioral sensitization induced by repeated acute exposure to cannabinoid agonists is associated with increased intracellular activation of CB 1 receptors in the caudate putamen and cerebellum (Rubino et al, 2003; see also Rubino et al, 2004), increased m-opioid receptor binding in the lateral thalamus and periaqueductal gray (PAG), and increased intracellular activation of m-opioid receptors in the nucleus accumbens (Viganò et al, 2005). Using a THC pre-exposure regimen that increases heroin intake in rats under an FR1 schedule, Ellgren et al (2007Ellgren et al ( , 2008 found lasting alterations of both the cannabinoid and opioid systems in rats exposed to THC during adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…An integrated horizontal CCD camera allowed controlling drop volumes for determining the deposited protein amounts. BrH stock was prepared according to the method described in Viganò et al [29] and stored at −20 • C. Aliquots from the stock were thawed and used for suspensions preparation right before the microspotting.…”
Section: Biotestsmentioning
confidence: 99%
“…E-mail: amelia.eisch@utsouthwestern.edu.1995, Uhl et al, 1999, Kreek et al, 2005. However, recent evidence points to a more novel role for MOR: regulating hippocampal structure and function (Morris and Johnston, 1995, Martinez and Derrick, 1996, Terman et al, 2000, Kearns et al, 2001, Harrison et al, 2002, Guo et al, 2005, Vigano et al, 2005a, Vigano et al, 2005b. MOR is expressed on interneurons and primary cell types in all hippocampal regions (Meibach and Maayani, 1980, Arvidsson et al, 1995, Mansour et al, 1995, Svoboda et al, 1999, Drake and Milner, 2002, including in the granule cell layer (GCL) of the dentate gyrus.…”
Section: Introductionmentioning
confidence: 99%